Digital Comic Media: Pancasila Relationships in Daily Life - Aprillia; Dewi, Ratna Sari; Setiawan, Sigit (Universitas Pendidikan Ganesha, 2022)
The position of learning media is very important as a tool in conveying material that the teacher cannot explain. However, often the use of learning media that are rarely used can harm teachers and students. This research aims to create a digital comic media of Pancasila relations in the daily life of Civics learning subjects in grade IV. This type of research is development research using the development stage of the Borg and Gall. The research subjects were two linguists, two material experts, and two media experts and student responses. Methods of data collection with interviews, observations, questionnaires, and documentation. The data collection instrument is a questionnaire instrument. The analysis technique is quantitative and qualitative analysis. The analysis results of linguists obtained 68% in the proper category. The results of material experts obtained a percentage of 79.41% in the feasible category. Expert validation results in a percentage of 85.62%, which fall into the very feasible category. The questionnaire participants' responses were 93.2% in the very feasible category. Thus, the digital comic media of Pancasila relations in everyday life deserves to be used. The implications of this research are expected to help teachers provide information to students related to Pancasila relationships in everyday life.